Exploring the causes of fear of foreign language learning: A pre-service case study - Palacios Alarcon, Ronny David; Dos Santos, Jardel Coutinho (Arandu UTIC, 2025)
Fear is a crucial variable that influences either positively or indirectly the acquisition of foreign languages, usually among teachers of language preservation. This research aims to explore the causes of fear in learning English as a foreign language (EFL) and how it manages to impact both on teaching and on the acquisition of the foreign language. The mixed method collected data from 19 participants who offered their services through surveys, interviews, and classroom observations. The results indicate that the most common fears a student may experience through language acquisition are fear of making mistakes, fear of negative evaluation, and fear of speaking in public, these barriers to creating effective communication through the use of English. These fears lead to lower levels of self-confidence and low participation. The study highlights the importance of implementing inclusive teaching methods, psychological support, and activities where they enable students to face their fears. It is crucial to address these issues in order to establish an effective and positive EFL learning environment.